2020
DOI: 10.12973/ijem.6.4.669
|View full text |Cite
|
Sign up to set email alerts
|

Tablet or Paper and Pen? Examining Mode Effects on German Elementary School Students’ Computation Skills with Curriculum-Based Measurements

Abstract: Progress monitoring of academic achievement is an essential element to prevent learning disorders. A prominent approach is curriculum-based measurement (CBM). Various studies have documented positive effects of CBM on students' achievement. Nevertheless, the use of CBM is associated with additional work for teachers. The use of tablets may be of help here. Yet, although many advantages of computer-or tablet-based assessments are being discussed in the literature (e. g. innovative item formats, adaptive testing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 39 publications
0
20
0
1
Order By: Relevance
“…Where the transition is smooth and successive, traditional face-to-face learning can coexist or is blended with the forms of distance learning. In contrast to the established gradual methods for planning and implementation of courses (Suartama et al, 2020), the transition from face-to-face to online courses observed in the COVID-19 pandemic was driven by an external factor and not by the pedagogical desire to make courses or computer applications (Blumenthal & Blumenthal, 2020) user friendly.…”
Section: Introductionmentioning
confidence: 96%
“…Where the transition is smooth and successive, traditional face-to-face learning can coexist or is blended with the forms of distance learning. In contrast to the established gradual methods for planning and implementation of courses (Suartama et al, 2020), the transition from face-to-face to online courses observed in the COVID-19 pandemic was driven by an external factor and not by the pedagogical desire to make courses or computer applications (Blumenthal & Blumenthal, 2020) user friendly.…”
Section: Introductionmentioning
confidence: 96%
“…In addition, children did not score significantly higher on either version. There was only a non-significant tendency for students to score higher in print mode, which was also found, for example, in Blumenthal and Blumenthal (2020). These differences might be due to the fact that children tended to work faster, albeit slightly less accurately, in the digital version.…”
Section: Discussionmentioning
confidence: 77%
“…In line with Blumenthal and Blumenthal (2020), we learned from the interviews that the participating children preferred the digital version. Although both versions were found to be fun, children perceived the digital version as being easier and more enjoyable than the print version.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, studies have generally shown that digital tests have been very well accepted by primary school teachers (Förster and Souvignier, 2014). For a digital maths tool, Blumenthal and Blumenthal (2020) analysed German fourth graders' opinions on print and digital modes of testing. They state that students found digital testing to be more motivating than testing in print form, and that students perceived digital tests as being faster and easier (although this perception was not corroborated by the test data).…”
Section: Digital Assessments In Primary Schoolmentioning
confidence: 99%